Classroom Interaction as a Way of Developing Students’ Speaking Skill at the Tertiary Level EFL Classroom: - Md. Nurullah Patwary; Swarna Chowdhury (Crossings, 2021)
Teaching speaking skills through classroom interaction is usually a neglected program at the tertiary EFL education in Bangladesh. This study primarily aims at discovering the current scenario of the practices and problems of classroom interaction at a Bangladeshi tertiary EFL classroom. This study further proposes some strategies for developing speaking skills through classroom interaction. The data were collected from 110 student respondents and 11 teacher respondents of 4 universities based on the stratified random sampling. For collecting and analyzing data, a mixed-methods approach (QUAN-QUAL) was applied. The data collection methods were a questionnaire survey on the tertiary EFL students and a semi-structured interview of the tertiary EFL teachers. The results show that though students and teachers were aware of classroom interaction, very little communication actually took place in the classroom because of teachers’ monopolizing the talk time and learners’ getting little to no talk time at all. The study also exposes that most of the students did not interact spontaneously and teachers used a great deal of Bangla in the EFL classroom. These hampered students’ speaking skills development. Finally, this paper presents some pedagogical implications and offers some recommendations for the considerations of the tertiary EFL teachers, learners, and policymakers